PSYCHOLOGICAL MEANINGFULNESS OF WORK EFFECTS ON ORGANIZATIONAL COMMITMENT IN HUMAN RESOURCE DEPARTMENT EMPLOYEE - Sylvia Diana Purba; Tivia Venica Tami Sitorus (Jurnal Bisnis Manajemen, 2022)
This study aims to determine the psychological meaningfulness of work and work engagement effect on organizational commitment. The convenience technique was used to collect data from 307 respondents with 123 and 184 from generations X and Y in the Human Resource Department (HRD) in Jakarta, Indonesia. Path analysis was conducted to diagnose effect of psychological meaningfulness and work engagement on organizational commitment, using SPSS and Macro Process Hayes 2013. The hypothesis test confirms that psychological meaningfulness significantly affects work engagement in the Y generation without affecting organizational commitment. Meanwhile, work engagement influences organizational commitment significantly and perfectly mediates the influences of psychological meaningfulness on organizational commitment. Conversely, psychological meaningfulness of work has a positive significant effect on work engagement and organizational commitment among the X generation. This study proves that the psychological meaningfulness of work in the Y generation has no significant increase in organizational commitment, with a rise in work engagement. Therefore, millennials are more challenged in carrying out their work with psychological meaningfulness of work.